2021
DOI: 10.1371/journal.pone.0256541
|View full text |Cite
|
Sign up to set email alerts
|

Consensus based framework for digital mobility monitoring

Abstract: Digital mobility assessment using wearable sensor systems has the potential to capture walking performance in a patient’s natural environment. It enables monitoring of health status and disease progression and evaluation of interventions in real-world situations. In contrast to laboratory settings, real-world walking occurs in non-conventional environments and under unconstrained and uncontrolled conditions. Despite the general understanding, there is a lack of agreed definitions about what constitutes real-wo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 48 publications
0
33
0
1
Order By: Relevance
“…Those results provided a proof-of-concept that free-living accelerometer data may be related to physical function, and recent evidence suggests that unsupervised assessments are necessary for acquiring real-world mobility data [ 48 , 51 ]. This is especially true, because gait characteristics from shorter walking bouts during daily living appear to be more informative about the disability level than longer bouts that are typically applied in laboratory-based tests [ 28 ].…”
Section: Opportunities For Using Motion Sensors In Msmentioning
confidence: 94%
“…Those results provided a proof-of-concept that free-living accelerometer data may be related to physical function, and recent evidence suggests that unsupervised assessments are necessary for acquiring real-world mobility data [ 48 , 51 ]. This is especially true, because gait characteristics from shorter walking bouts during daily living appear to be more informative about the disability level than longer bouts that are typically applied in laboratory-based tests [ 28 ].…”
Section: Opportunities For Using Motion Sensors In Msmentioning
confidence: 94%
“…The PI signals were used to isolate the different walking bouts [defined as comprising of at least two right and two left strides ( Kluge et al, 2021 )] and all reference GEs ( r GEs) were identified according to the methodology proposed and validated by Salis et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…As part of an observational study (Mobilise-D [24]), a convenience sample of 108 participants were recruited from six cohort groups that included older healthy adults (HA) and participants with potentially altered mobility due to Parkinson's Disease (PD), Multiple Sclerosis (MS), Proximal Femoral Fracture (PFF), Chronic Obstructive Pulmonary Disease (COPD) or Congestive Heart Failure (CHF). Besides other inclusion and exclusion criteria [25], participants were able to walk four meters and had no comorbidities impacting mobility. Data were collected across ve gait laboratories after receiving written informed consent (Ethics approvals: The Newcastle upon Tyne Hospitals NHS Foundation Trust and She eld Teaching Hospitals NHS Foundation Trust: London -Bloomsbury Research Ethics committee, 19/LO/1507; Tel Aviv Sourasky Medical Center: the Helsinki Committee, 0551-19TLV; Robert Bosch Foundation for Medical Research: medical faculty of the University of Tübingen, 647/2019BO2; University of Kiel: medical faculty of Kiel University, D540/19).…”
Section: Data Collectionmentioning
confidence: 99%
“…Data were collected across ve gait laboratories after receiving written informed consent (Ethics approvals: The Newcastle upon Tyne Hospitals NHS Foundation Trust and She eld Teaching Hospitals NHS Foundation Trust: London -Bloomsbury Research Ethics committee, 19/LO/1507; Tel Aviv Sourasky Medical Center: the Helsinki Committee, 0551-19TLV; Robert Bosch Foundation for Medical Research: medical faculty of the University of Tübingen, 647/2019BO2; University of Kiel: medical faculty of Kiel University, D540/19). Participant demographics were collected, and patient characterisation was completed based on clinical assessments speci c to each cohort [25] (Table 1). Experimental Protocol…”
Section: Data Collectionmentioning
confidence: 99%